2023
DOI: 10.1186/s13018-023-03729-1
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral bone quality score to predict cage subsidence following oblique lumbar interbody fusion

Abstract: Background Current evidence suggests that the magnetic resonance imaging (MRI)-based vertebral bone quality (VBQ) score is a good parameter for evaluating bone quality. We aimed to assess whether the VBQ score can predict the occurrence of postoperative cage subsidence after oblique lumbar interbody fusion (OLIF) surgery. Methods Patients (n = 102) who had undergone single-level OLIF with a minimal follow-up for 1 year were reviewed in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Hu et al correlated VBQ scores with subsidence and showed that VBQ scores were moderately correlated with DXA T-scores for the total hip and lumbar spine ( P <0.001), had a moderate correlation with the amount of cage subsidence ( P <0.001), and were able to significantly predict cage subsidence with an accuracy of 85.6% after transforaminal lumbar interbody fusion (TLIF) 6 . VBQ has since been shown to be significantly associated with cage subsidence after oblique lumbar interbody fusion (OLIF) 5 . There has been 1 previous study assessing cervical VBQ and subsidence; however, those authors measured subsidence on postoperative x-rays rather than CT scans 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hu et al correlated VBQ scores with subsidence and showed that VBQ scores were moderately correlated with DXA T-scores for the total hip and lumbar spine ( P <0.001), had a moderate correlation with the amount of cage subsidence ( P <0.001), and were able to significantly predict cage subsidence with an accuracy of 85.6% after transforaminal lumbar interbody fusion (TLIF) 6 . VBQ has since been shown to be significantly associated with cage subsidence after oblique lumbar interbody fusion (OLIF) 5 . There has been 1 previous study assessing cervical VBQ and subsidence; however, those authors measured subsidence on postoperative x-rays rather than CT scans 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A common complication of interbody fusion is subsidence, defined as the sinking of the interbody cage into 1 or both of the adjacent vertebral bodies 1–4 . Risk factors for subsidence include older patient age, 5 endplate morphology, 5 excessive endplate removal and incidental fracture, 6,7 cage position and height, 6,8 lower screw tip-to-vertebral body height 7 and graft-to-endplate surface area ratios, 8 smoking, 9 and low bone mineral density (BMD) 10,11 . The existing body of literature contains conflicting reports on the clinical effects of subsidence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The study found a significant correlation between VBQ and BMD [ 16 ]. Many researchers have used VBQ as an indicator to assess cage subsidence and recurrence after lumbar fusion surgery [ 7 , 17 ]. However, deformities, fractures, hemangiomas and local infections of the lumbar spine may affect the L1-4VBQ score.…”
Section: Introductionmentioning
confidence: 99%